2012
DOI: 10.2319/091812-742.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of text message follow-up on patient's self-reported level of pain and anxiety

Abstract: Objectives: To determine whether a text message reduces the severity of patient self-reported levels of pain and anxiety following initial placement of orthodontic appliances. Materials and Methods: Thirty-nine orthodontic patients were randomly assigned to one of two groups and matched for age, gender, and bracket type (self-ligating vs conventional). The subjects completed baseline questionnaires to ascertain their levels of pain and anxiety before initiating orthodontic treatment. Following the initial appo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 27 publications
1
46
0
2
Order By: Relevance
“…24 Patients usually experience pain, discomfort, and anxiety, and also are given dietary advice by orthodontists during the initial stage of fixed orthodontic treatment. 3,25,26 These experiences can cause acute stress and nutritional changes and may thus increase the production of corticotrophin-releasing hormone, leading to an aberration in the menstrual cycle during the first month of wearing fixed orthodontic appliances. 27 In this study, after patients got used to the treatment and dietary changes, the menstrual aberration reverted to normal in subsequent menstrual cycles as anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…24 Patients usually experience pain, discomfort, and anxiety, and also are given dietary advice by orthodontists during the initial stage of fixed orthodontic treatment. 3,25,26 These experiences can cause acute stress and nutritional changes and may thus increase the production of corticotrophin-releasing hormone, leading to an aberration in the menstrual cycle during the first month of wearing fixed orthodontic appliances. 27 In this study, after patients got used to the treatment and dietary changes, the menstrual aberration reverted to normal in subsequent menstrual cycles as anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…(20,21,22,23) Additionally, follow-up text message sent from an orthodontic office following initial appliance placement resulted in patient's lower levels of selfreported pain. (24) Another study showed that text message reminders to parents of orthodontic patients were shown to be an effective way to improve oral hygiene in these patients. (25) With the introduction of text messaging, it has become easier to communicate with the patient.…”
Section: Introductionmentioning
confidence: 99%
“…23 Text messages sent from the orthodontic office following the initial appliance placement resulted in a lower level of self-reported pain. 25 Another study showed that text message reminders to parents of orthodontic patients were shown to be an effective way to improve oral hygiene in these patients. 26 The increase of ownership of mobile phones along with the popularity of text messaging as a preferred means of communication ensures comprehensive access to target groups.…”
Section: Introductionmentioning
confidence: 99%